2014
DOI: 10.4161/viru.27794
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of bacterial virulence gene expression by molecular oxygen and nitric oxide

Abstract: Molecular oxygen (O 2 ) and nitric oxide (NO) are diatomic gases that play major roles in infection. The host innate immune system generates reactive oxygen species and NO as bacteriocidal agents and both require O 2 for their production. Furthermore, the ability to adapt to changes in O 2 availability is crucial for many bacterial pathogens, as many niches within a host are hypoxic. Pathogenic bacteria have evolved transcriptional regulatory systems that perceive these gases and respond by reprogramming gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 286 publications
(211 reference statements)
1
67
0
2
Order By: Relevance
“…Reactive oxygen is generated by animal innate immune systems in a bacterial infection (49). The E. coli electron transport mutations that induce bacterial response pathways such as the SoxRS and OxyR pathways may mimic E. coli in its pathogenic state in an infection, where ROS is an indication of an animal immune response.…”
Section: (E) Feedingmentioning
confidence: 99%
“…Reactive oxygen is generated by animal innate immune systems in a bacterial infection (49). The E. coli electron transport mutations that induce bacterial response pathways such as the SoxRS and OxyR pathways may mimic E. coli in its pathogenic state in an infection, where ROS is an indication of an animal immune response.…”
Section: (E) Feedingmentioning
confidence: 99%
“…Pathogenic bacteria have evolved transcriptional regulatory systems that perceive such hostile conditions and respond by reprogramming gene expression [7,8]. Defensive mechanisms that detoxify ROS and RNS and repair damaged cell components essential for the intracellular survival of the pathogen during infection are strictly regulated in pathogens [7,71].…”
Section: Implications Of Iscr In Host-pathogen Interactionsmentioning
confidence: 99%
“…Pathogenic bacteria rely on transcriptional regulatory systems to perceive such hostile conditions during host invasion and respond by reprogramming gene expression [7,8]. It has been recently shown that IscR functions as virulence factor in several pathogenic bacteria, modulating gene expression for an adequate response to the stress conditions at the host-pathogen interface [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, Mtb uses two distinct redox couples, mycothiol and ergothioneine, and harbors at least 50 proteins containing Fe–S clusters that facilitate an intercellular life cycle [37, 175]. Interestingly, Mtb has a higher incidence of Fe–S cluster proteins (~6.5 motifs/1000 ORFs) than other aerobic bacteria (2.8 motifs/1000 ORFs), underscoring the importance of Fe–S cluster proteins to pathogenic adaptations of Mtb [176, 177].…”
Section: Mtb Gas Sensorsmentioning
confidence: 99%